Mastering Magento 2 maximize the power of Magento 2 to create productive online stores - Williams, Bret; Bownds, Jonathan (Packt Publishing, 2016)
Maximize the power of Magento 2 to create productive online stores About This Book Updated for Magento 2, this book offers a comprehensive coverage of all the new features of Magento to build modern online stores Exploit little-known techniques to extend, tune, and manage your Magento installation Detailed coverage to make your store run faster, better, and more productively Who This Book Is For This book is for web designers, developers, or e-commerce store-owners who design or manage Magento stores for their clients and want to gain an in-depth understanding of the various features of Magento 2. What You Will Learn Discover what makes Magento 2 different - and even more powerful Develop strategies to create multi-store environments Find out how to create themes and extend the functionality of Magento 2 Create sound development practices to insure code integrity and security Know the why, as well as the how, behind using Magento 2 In Detail The long-awaited release of the world's most popular online solution, Magento 2, is now out with an all new interface and several enhancements. This book offers you advanced guidance on managing, optimizing, and extending your store while taking advantage of the new features of Magento 2. This is a comprehensive guide to using the all new features and interface of Magento 2 to build, extend, and design online stores. From planning your Magento installation through to advanced techniques designed to make your store as successful as possible, this book is your roadmap to managing your Magento store. Focusing on Magento's Community version, the book covers everything from creating and managing multiple stores to fine-tuning Magento for speed and performance. You'll learn how to manage categories, products, design themes, extensions, and more. Style and Approach This book will be a straightforward guide that will dive deep into both aspects of developing and administering beautiful and secure stores. Get a firm idea of the different tools that the latest version has to offer to ensure the best customer experience.
Includes index. - Description based on online resource; title from cover (Safari, viewed July 13, 2016)
Keywords: Magento (Web site development tool); Electronic commerce; Commerce électronique; COMPUTERS / General